2013
DOI: 10.1603/ec12233
|View full text |Cite
|
Sign up to set email alerts
|

Development of Insecticide Resistance in Field Populations of <I>Brevicoryne brassicae</I> (Hemiptera: Aphididae) in Pakistan

Abstract: Cabbage aphid Brevicoryne brassicae (L.) (Hemiptera: Aphididae) is a serious pest of crucifers in Pakistan. After incidences of poor control by recommended insecticides, the current study was undertaken to find out the status of insecticide resistance in Pakistani B. brassicae. Apterous adult aphids were bioassayed from 2006 to 2010 for their response to 12 insecticides using an adult immersion method. No or very low levels of resistance was found to endosulfan; and the organophosphates: chlorpyrifos and profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 14 publications
1
20
0
3
Order By: Relevance
“…They reported that the treated insect with Azadirachta indica extract usually cannot molt to its next life stage and dies within a few days and acts primarily as a repellent when applied to a plant, and may kill an insect within 24 hrs ( Table 2). The obtained results were in agreement with those of Ahmad and Akhtar [18]. They reported that aphids developed resistance against chemical insecticides including pyrethroids (cypermethrin, lambdacyhalothrin, bifenthrin and deltamethrin) and neonicotinoids (imidacloprid, acetamiprid, and thiamethoxam).…”
Section: Effect Of Botanicals Against Cabbage Aphidsupporting
confidence: 90%
“…They reported that the treated insect with Azadirachta indica extract usually cannot molt to its next life stage and dies within a few days and acts primarily as a repellent when applied to a plant, and may kill an insect within 24 hrs ( Table 2). The obtained results were in agreement with those of Ahmad and Akhtar [18]. They reported that aphids developed resistance against chemical insecticides including pyrethroids (cypermethrin, lambdacyhalothrin, bifenthrin and deltamethrin) and neonicotinoids (imidacloprid, acetamiprid, and thiamethoxam).…”
Section: Effect Of Botanicals Against Cabbage Aphidsupporting
confidence: 90%
“…However, regular use of chemical pesticides including methomyl, emamectin benzoate and pyrethroids has led to the aphids developing resistance to most of these chemicals [3]. Chemical fertilizers and pesticides accumulate in plants and plant products, causing health problems in humans due to biomagnifications [4].…”
Section: Introductionmentioning
confidence: 99%
“…The use of pesticides is currently a widely adopted strategy to manage B. brassicae field infestations. Such excessive pesticide usage on directly consumed, short‐duration vegetable crops ahead of harvest could harm human and ecosystem health (Theiling & Croft, ) and contributes to the development of rapid resistance to insecticides (Ahmad & Akhtar, ). The use of Bacillus as a potential indirect biological control agent of cabbage aphids has not been explored.…”
Section: Introductionmentioning
confidence: 99%